Maqasid Syariah Perspective Abu Hamid Muhammad Bin Muhammad Al-Ghazali - Dayrobi, Mhd; Tanjung, Dhiauddin (AMK : Abdi Masyarakat UIKA, 2024)
Maqasid sharia, if traced from its development, has existed since the time of Rasulullah SAW. Even though at that time the theme of maqasid syari'ah had not been clearly stated, at least maqasid syari'ah had provided color and contribution to Islamic legal legislation in accordance with the objectives of establishing Islamic law. This research aims to describe Imam Ghazali's thoughts regarding maqasid Sharia. This research is library research and is included in descriptive research and is a type of bibliographic research because it tries to collect data, describe and analyze Imam al Ghazali's thoughts regarding maqashid sharia. In this research, it is concluded that Imam al-Ghazali's Maqasid Syari'ah Thought can be traced from his books, especially in the book al-Mustasfa min Ilmi al-Usul. He classifies maslahah based on whether the syara' is accepted or not accepted into 3 (three) types, namely Maslahat al-mu'tabarah (benefits that are justified by the syara'), Maslahat mulgah (benefits that are rejected by the nashsyara'), and Maslahah murlahah (benefits that are not justified and not canceled by Sharia'). Al Ghazali also divided the levels of maqasid sharia into 3 (three), namely the levels of daruriyah (primary needs), al-hajjiyat (secondary needs) and tahsiniyat (tertiary needs). Of these three levels, only the emergency level can serve as a guide in determining Islamic law. Meanwhile, at the hajiyat and tahsiniyat levels, they cannot be used as guidelines in determining laws unless they are strengthened by evidence.